PENGARUH GOOD CORPORATE GOVERNANCE DAN RETURN ON ASSETS TERHADAP TAX AVOIDANCE - Jefri Jefri; Yaumil Khoiriyah (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
The objective of this research was to prove empirically the factors affecting the good corporate governance and the return on assets on the tax avoidance of the manufacturing companies indexed in the Indonesia Stock Exchange in the period of 2014-2016. The independent variables of this research were the institutional ownership, the managerial ownership, the proportion of independent board of Commissioners, the audit committee, the audit quality, the return on assets; while, the dependent variable of this research was the tax avoidance. The data collecting technique used in this research was the purposive sampling. The number of sample used in this research was 57 manufacturing companies indexed in the Indonesia Stock Exchange in 2014-2016. The data analysis technique used in this research was the multiple linear regression by using IBM SPSS Version 20 program. The result of this research showed that the managerial ownership, the audit quality, and the return on assets affected the tax avoidance; while, the institutional ownership, the proportion of independent board of commissioners, and the audit committee did not have any effect on the tax avoidance.